Theorizing animal–computer interaction as machinations. Issue 98 (February 2017) - Aspling, Fredrik; Juhlin, Oskar
Abstract: The increased involvement of animals in digital technology and user-computer research opens up for new possibilities and forms of interaction. It also suggests that the emerging field of Animal–Computer Interaction (ACI) needs to reconsider what should be counted as interaction. The most common already established forms of interaction are direct and dyadic, and limited to domesticated animals such as working dogs and pets. Drawing on an ethnography of the use of mobile proximity sensor cameras in ordinary wild boar hunting we emphasize a more complex, diffuse, and not directly observable form of interaction, which involves wild animals in a technological and naturalistic setting. Investigating human and boar activities related to the use of these cameras in the light of Actor-Network Theory (ANT) and Goffman's notion of strategic interaction reveals a gamelike interaction that is prolonged, networked and heterogeneous, in which members of each species is opposed the other in a mutual assessment acted out through a set of strategies and counter-strategies. We stress the role of theory for the field of ACI and how conceptualizations of interaction can be used to excite the imagination and be generative for design. Seeing interaction as strategies and acknowledging the existence of complex interdependencies could potentially inspire the design of more indirect and non-dyadic interactions where a priori simplifications of design challenges as either human or animal can be avoided. Highlights: We present an ethnography of the use of mobile proximity sensor cameras in boar hunting. We stress the role of theory in Animal–Computer Interaction (ACI) and discuss the concept of interaction. We show how Actor-Network Theory (ANT) and strategic interaction can be combined to reveal and account for interactions that are indirect, heterogeneous, prolonged, and networked. We introduce concepts such as ontological symmetry, delegation, and program and anti-program, and show how interaction can be understood as strategies. We discuss how the theoretical foundations offered by ANT and strategic interaction can be generative in ACI design.